PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 28 BENGKALIS - Bella, Nurna; Lazim N, Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Problem in this research is the low student learning outcomes IPA IV grade publik school students 28 Bengkalis. With an average of 63,75. Within minimal completeness criterion stated is 66,7. Among 20 student there was only 7 students were able to achieve the score of KKM. It is a Classroom Action Research (CAR) by two cycles. The purpose of this study to improve science learning outcomes of public school fourth graders 28 Bengkalis with direct learning model application. In cycle I, the percentage of teachers activity in first meeting is adquate 55%. In second meeting, teachers activity significantly increased to 70% with good category. In cycle II, first meeting was in good category 80% and second meeting a very good category 85%. Meanwhile, the activity of student?s also improved, in cycle I the percentage the activity of student?s in first meeting is adquate 55%. In second meeting, activity of student?s significantly increased to 70% with good category. In cycle II, first meeting was in good category 75% and second meeting indicates a very good category 85%. The student?s social science learning result from the average grades before action was 63,75 increased at cycle I to be 73 with the percentage increase by 14,51% and at cycle II the average grades increased to be 78,75 with the percentage increase by 23,53% from the basic score by 63,75. Based on the result in can be concluded that implementation of direct instruction model can social in four graders at SDN 28 Bengkalis.Key words: model direct instruction, Learning result of science subject